Nurses’ Perceptions of Deep Breathing Therapy for Angina Pectoris Patients at RSUD Umar Wirahadikusumah: A Phenomenological Study - Prinsesa Mutiara Adam; Diding Kelana Setiadi; Ayu Prameswari Kusuma Astuti (INDOGENIUS, 2026)
Angina pectoris is a common clinical manifestation of coronary heart disease that causes chest pain and discomfort, requiring comprehensive nursing management. Deep breathing therapy is a non-pharmacological nursing intervention that may help reduce pain and improve patient comfort. This study aimed to explore nurses’ perceptions regarding the application of deep breathing therapy in patients with angina pectoris. A qualitative study with a transcendental phenomenological approach was conducted in the High Care Cardiac Unit of a regional public hospital in Indonesia. Five nurses were recruited as participants using a snowball sampling technique. Data were collected through face-to-face, in-depth interviews guided by semi-structured questions. All interviews were audio-recorded, transcribed verbatim, and analyzed using Creswell’s spiral data analysis combined with Moustakas’ phenomenological analysis steps to identify meaningful themes. The findings indicated that nurses perceived deep breathing therapy as a simple, safe, and independent nursing intervention that could be flexibly applied according to patients’ clinical conditions. The therapy was mainly used for patients with mild to moderate chest pain and was perceived to promote relaxation, reduce anxiety, and enhance patient comfort. However, nurses also reported several limitations, including reduced effectiveness in patients with severe pain, unstable hemodynamic conditions, heavy nursing workload, and the absence of specific clinical guidelines. In conclusion, deep breathing therapy is perceived by nurses as a beneficial supportive intervention in the management of angina pectoris, highlighting the need for the development of standardized guidelines and further strengthening of non-pharmacological nursing practices in cardiovascular care.